The effect of foliar spraying with NPK on the growth of Olive transplants Olea europea L. variety Khudhery. - AlRubayee Sabbah ِAbd Flayyh; AlAsady, Alaa Abbas; Aziz, Harith Mahmoud; Falhi, Manar Abd (Journal of Kerbala for Agricultural Sciences, 2018)
The research was conducted in Karbala University’s farm for season 2006-2007, included five treatments (control, twice spraying with NPK, three spraying with NPK, four spraying with NPK and five spraying with NPK). The research designed as factorial in R.C.B.D. and L.S.D. compared with 0.05 probability. The results showed the treatment S3 was the best in (Plant height, Plant diameter and chlorophyll) while the treatment S4 was the best than other treatments with (branch length, branch number, leaf area, % dry matter, % CHO in leaves, % N and % K). The % P had no significant effect on all treatments.